Heidegger, Dilthey, and the crisis of historicism - Bambach, Charles R. (Cornell University Press, 1995)
Bambach's account of the demise of historicism within the context of German metaphysics provides a new perspective on the development of Heidegger's concept of ""historicity"" and on the origins of postmodern thought.
Keywords: Heidegger, Martin, -- 1889-1976.; Dilthey, Wilhelm, -- 1833-1911.; Heidegger, Martin, -- 1889-1976 -- Et l'historicisme.; Dilthey, Wilhelm, -- 1833-1911 -- Et l'historicisme.; Windelband, W. -- (Wilhelm), -- 1848-1915.; Rickert, Heinrich, -- 1863-1936.; Dilthey, Wilhelm, -- 1833-1911; Heidegger, Martin, -- 1889-1976; Dilthey, Wilhelm -- 1833-1911; Heidegger, Martin -- 1889-1976; Rickert, Heinrich -- 1863-1936; Windelband, Wilhelm -- 1848-1915; Heidegger, Martin.; Dilthey, Wilhelm.; Historicism.; Philosophy, German -- 19th century.; Philosophy, German -- 20th century.; Historicisme.; Philosophie allemande -- 19e siècle.; Philosophie allemande -- 20e siècle.; historicism (theory); HISTORY -- Historiography.; Historicism; Philosophy, German; Historismus; Historizismus; Krise; Historisme.; 1800-1999